Atezolizumab and bevacizumab, with or without radiotherapy, versus docetaxel in patients with metastatic non-small cell lung cancer previously treated with a checkpoint inhibitor and chemotherapy: results from the randomized, phase Ib/II MORPHEUS-Lung study - Enriqueta Felip; Francois Ghiringhelli; Alona Zer; Byoung Chul Cho; Sun Min Lim; Laurent Greillier; Alastair Greystoke; Nuria Pardo; Yaacov R Lawrence; Nedal Al-Sakaff; Hans-Joachim Helms; Hen Prizant; et al. (Journal for ImmunoTherapy of Cancer)
Background Options remain limited for patients requiring later lines of therapy for metastatic non-small cell lung cancer (mNSCLC) due to poor prognosis and potential toxicities. Therefore, trials of novel combinations of existing therapeutic candidates are warranted. Here, we report robust interim analysis results from the MORPHEUS-Lung study in immune checkpoint inhibitor (CPI)-exposed patients with non-squamous mNSCLC and without targetable gene mutations.Methods MORPHEUS-Lung enrolled patients with disease progression during or following treatment with a platinum-containing regimen and a PD-L1/PD-1 immune CPI, given in combination as one line or as two separate lines of therapy, regardless of PD-L1 expression. The primary efficacy endpoint was objective response rate (ORR). Secondary efficacy endpoints included progression-free survival, duration of response, disease control rate, overall survival, and safety; exploratory endpoints included biomarkers. Patients were randomized to the atezolizumab+bevacizumab+non-ablative stereotactic body radiotherapy (SBRT), atezolizumab+bevacizumab, or docetaxel (control) arms and included in this analysis.Results At data cut-off (August 28, 2024), 121 patients were randomized and treated: atezolizumab+bevacizumab+SBRT (n=42), atezolizumab+bevacizumab (n=40), and docetaxel (n=39). Confirmed ORR was 16.7% (6/36), 20.0% (8/40), and 12.8% (5/39) in the atezolizumab+bevacizumab+SBRT, atezolizumab+bevacizumab, and docetaxel (control) arms, respectively; one patient (2.5%) in the atezolizumab+bevacizumab arm had a complete response. Grade≥3 adverse events (AEs) occurred in 47.6% (20/42) of patients receiving atezolizumab+bevacizumab+SBRT, 45.0% (18/40) receiving atezolizumab+bevacizumab, and 64.1% (25/39) receiving docetaxel. AEs leading to discontinuation of any treatment occurred in 14.3% of patients in the atezolizumab+bevacizumab+SBRT arm, 7.5% in the atezolizumab+bevacizumab arm, and 15.4% in the docetaxel (control) arm. There were no clear correlations of response or survival benefit with PD-L1 expression or immune phenotype.Conclusions Results from this interim analysis suggest that atezolizumab+bevacizumab, with or without SBRT, showed evidence of numerically improved efficacy outcomes compared with docetaxel, with a trend toward a benefit in both the primary and secondary resistance settings. Safety was consistent with the known profiles of the individual drugs, with increased toxicity observed when SBRT was added to atezolizumab+bevacizumab.